Enhanced mechanical properties of Q-carbon nanocomposites by nanosecond pulsed laser annealing. (11th September 2018) - Gupta, Siddharth; Sachan, Ritesh; Bhaumik, Anagh; Narayan, Jagdish
Abstract: Q-carbon is a metastable phase of carbon formed by melting and subsequently quenching amorphous carbon films by a nanosecond laser in a super undercooled state. As Q-carbon is a material harder than diamond, it makes an excellent reinforcing component inside the softer matrix of a composite coating. In this report, we present a single-step strategy to fabricate adherent coatings of hard and lubricating Q-carbon nanocomposites. These nanocomposites consist of densely-packed sp 3 -rich Q-carbon (82% sp 3 ), and sp 2 -rich α -carbon (40% sp 3 ) amorphous phases. The nanoindentation tests show that the Q-carbon nanocomposites exhibit a hardness of 67 GPa (Young's modulus ∼ 840 GPa) in contrast to the soft α -carbon (hardness ∼ 18 GPa). The high hardness of Q-carbon nanocomposites results in 0.16 energy dispersion coefficient, in comparison with 0.74 for α -carbon. The soft α -carbon phase provides lubrication, resulting in low friction and wear coefficients of 0.09 and 1 × 10 −6, respectively, against the diamond tip. The nanoscale dispersion of hard Q-carbon and soft α -carbon phases in the Q-carbon nanocomposites enhances the toughness of the coatings. We present detailed structure-property correlations to understand enhancement in the mechanical properties of Q-carbon nanocomposites. This work provides insights into the characteristics of Q-carbon nanocomposites and advances carbon-based superhard materials for longer lasting protective coatings and related applications.